Pembentukan karakter religius perspektif Surat Al-Kafirun - Dia Hidayati Usman; Amir Faishol Fath (LPPM Universitas Ibn Khaldun, Bogor, 2020)
This study aims to formulate tauhidic education by focusing on surat al-Kafirun in the interpretation of